Evaluating inclusive teacher competences: a systematic review within the training courses for special education specialization in Italy - De Angelis, Marta (Form@re - Open Journal per la formazione in rete, 2021)
Teacher education is of primary importance in the creation of an equitable and inclusive school system, allowing teachers the opportunity to acquire the necessary skills to respond adequately to the different needs of all pupils. In Italy, in the context of training courses for the achievement of specialization for educational support activities for pupils with disabilities, different methods are used to evaluate the effectiveness of these courses and, in particular, the skills acquired at the end of the training. The aim of the work is to carry out a systematic review of the tools used, in Italy, to assess student skills at the end of the training course, as well as the competence profiles to which they refer. To this end, N=12 primary studies published in open access from 2011 to 2020 were taken into consideration. The descriptive summary obtained from the review can be useful for creating shared evaluation models and learning outcomes for teachers who specialize in the activities of didactic support. Valutare le competenze del docente inclusivo: revisione sistematica nei corsi di specializzazione sul sostegno in Italia La formazione degli insegnanti assume oggi una primaria importanza nella realizzazione di un sistema scolastico equo e inclusivo, consentendo ai docenti la possibilità di acquisire le necessarie competenze per rispondere in maniera congrua alle diverse esigenze di tutti gli alunni. In Italia, nell’ambito dei percorsi di formazione per il conseguimento della specializzazione per l’attività di sostegno didattico agli alunni con disabilità, differenti sono le modalità impiegate per valutare l’efficacia dei suddetti corsi e, in particolare, le competenze acquisite alla fine del percorso formativo. L’obiettivo del lavoro è dunque quello di delineare, mediante una revisione sistematica, un quadro comparativo degli strumenti utilizzati per valutare le competenze dei corsisti alla fine del percorso formativo, nonché i profili di competenza cui si riferiscono. A tal fine, sono stati presi in considerazione N=12 studi primari pubblicati in open access dal 2011 al 2020. La sintesi descrittiva ricavata dall’indagine può essere utile per realizzare modelli di valutazione e learning outcomes condivisi per i docenti che si specializzano nelle attività di sostegno didattico.